2021
DOI: 10.3390/languages6010046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceptions: Instructor–Student Dynamics in the Spanish Heritage Classroom

Abstract: The rising population of heritage speakers (HS) in university courses in the US has increased the need for instructors who understand the linguistic, social, and cultural profiles of their students. Recent research has discussed the need for specialized courses and their differentiation from second-language (L2) classes, as well as the intersection between HS and language attitudes. However, prior studies have not examined HS students’ language attitudes toward the sociolinguistic background of the instructors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The survey results showed that current SHL teachers are mostly native speakers of the language (56% of respondents), often entering the teaching profession opportunistically-being recruited only because they speak Spanish (Gironzetti & Belpoliti, 2018), while only 5% of the respondents identified themselves as SHL speakers. This finding highlights the lack of representation of heritage speakers in the SHL teacher pool, which may impact students' motivation, engagement, and achievement (Egalite et al, 2015;González Darriba et al, 2021;Guzman, 2020). Early engagement programs dedicated to fostering interest in language teaching among SHL speakers at the high school level could result in a relevant shift, with larger number of SHL learners becoming the future practitioners in the field, thus serving the trifold purpose of helping them and their students to maintain, value, and expand their use of the language (Bustamante & Novella, 2019;Guzman, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The survey results showed that current SHL teachers are mostly native speakers of the language (56% of respondents), often entering the teaching profession opportunistically-being recruited only because they speak Spanish (Gironzetti & Belpoliti, 2018), while only 5% of the respondents identified themselves as SHL speakers. This finding highlights the lack of representation of heritage speakers in the SHL teacher pool, which may impact students' motivation, engagement, and achievement (Egalite et al, 2015;González Darriba et al, 2021;Guzman, 2020). Early engagement programs dedicated to fostering interest in language teaching among SHL speakers at the high school level could result in a relevant shift, with larger number of SHL learners becoming the future practitioners in the field, thus serving the trifold purpose of helping them and their students to maintain, value, and expand their use of the language (Bustamante & Novella, 2019;Guzman, 2020).…”
Section: Discussionmentioning
confidence: 97%